2023
DOI: 10.3390/plants12102052
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome and Metabolome Analyses Reveal Details of the Molecular Regulation of Resistance to Stem Nematode in Sweet Potato

Abstract: Stem nematode disease can seriously reduce the yield of sweet potato (Ipomoea batatas (L.) Lam). To explore resistance mechanism to stem nematode in sweet potato, transcriptomes and metabolomes were sequenced and compared between two sweet potato cultivars, the resistant Zhenghong 22 and susceptible Longshu 9, at different times after stem nematode infection. In the transcriptional regulatory pathway, mitogen-activated protein kinase signaling was initiated in Zhenghong 22 at the early stage of infection to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Integrated analyses of transcriptomes and metabolomes are now widely used to identify key differences in regulatory mechanisms between stress-tolerant and -sensitive genotypes displaying differential phenotypes, and relevant studies have shown that plants respond to drought stress mainly by regulating oxidative balance, signal transduction, plant hormones and energy metabolism [24][25][26][27][28]. In sweet potato, transcriptomics has become a powerful tool for examining various mechanisms, such as potassium-deficiency tolerance [29], skin color [30], and stem nematode resistance [31]. In this study, we used integrated transcriptome-metabolome analyses to reveal the molecular differences between drought-sensitive and drought-tolerant sweet potato cultivars under drought stress, providing further insights into the drought tolerance mechanisms of this important crop.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated analyses of transcriptomes and metabolomes are now widely used to identify key differences in regulatory mechanisms between stress-tolerant and -sensitive genotypes displaying differential phenotypes, and relevant studies have shown that plants respond to drought stress mainly by regulating oxidative balance, signal transduction, plant hormones and energy metabolism [24][25][26][27][28]. In sweet potato, transcriptomics has become a powerful tool for examining various mechanisms, such as potassium-deficiency tolerance [29], skin color [30], and stem nematode resistance [31]. In this study, we used integrated transcriptome-metabolome analyses to reveal the molecular differences between drought-sensitive and drought-tolerant sweet potato cultivars under drought stress, providing further insights into the drought tolerance mechanisms of this important crop.…”
Section: Introductionmentioning
confidence: 99%